Supply Chain Optimization in Agribusiness Curly Chili (Capsicum annum L.) in Kendari City - Muh. Bintang Alfarizy; Surni, Surni; Abdi, Abdi (International Journal of Technology and Education Research, 2024)
This research aims to (1) determine the flow of goods, financial flow and information flow of curly chilies in Kendari City, (2) determine the marketing margin for curly chilies in Kendari City, (3) determine the efficiency of curly chili marketing channels in Kendari City. This research was conducted in Kendari City from January to April 2024. This research used descriptive analysis, marketing margin analysis, and marketing efficiency (Farmer's Share). The number of curly chili farmer respondents was 10 people using the census technique, collecting traders were 2 people and retailers were 8 people using the snowball sampling technique. Based on the research results, it shows that (1) Flow of goods, financial flow and information flow, namely: flow of production from farmers to collectors of 200 kg, collectors to retailers of 175 kg and retailers to consumers of 150 kg. The flow of money from collectors to farmers is IDR 5,800,000, retailers to collectors is IDR 5,925,000 and retailers to consumers is IDR 7,650,000, and the flow of information between farmers and collectors is 2 times, collectors and retailers are 2 times, retailers and consumers are carried out directly when a transaction is occurring or in progress (2) the marketing margin obtained for curly chilies at the collecting trader level is IDR 10,500 / kg and at the retailer level it is IDR 11,500 / kg. (3) The results of the analysis regarding the percentage of price share received by producers (farmer's share) for collecting traders is 74% and retail traders are 78. This shows that the curly chili marketing channel in Kendari City is running efficiently with a percentage of 76%.